Rapid Body-Wide Transcriptomic Turnover During Rhesus Macaque Perinatal Development - Zhang, Wenqian; Wang, Wei; Zhao, Manman; Turck, Christoph W.; Zhu, Ying; Wang, Guang-Zhong (Frontiers in Physiology, 2021)
An hourglass cup-shape pattern of regulation at the molecular level was detected during the development of the primate brain. Specifically, a peak of temporally differentially expressed genes around the time of birth has been observed in the human brain. However, to what extend this peak of regulation exists among species has not been investigated in great detail. Here, by integrating multiple large-scale transcriptome data from rhesus macaques, we confirmed that a similar differential expression peak exists during the development of the macaque brain. We also found that a similar peak exists during the development of other organs, such as liver, testis, kidney and heart. Furthermore, we found that distinct pathways are regulated in the peak period of those organs. Our results highlight the importance of co-evolution of diverse organs during critical periods of perinatal development in primates.